A phase Ib combination study of RO4929097, a gamma-secretase inhibitor, and temsirolimus in patients with advanced solid tumors - Diaz-Padilla, Ivan (Springer US, 2013)
Background To determine the recommended phase II dose (RP2D) and assess the safety, pharmacokinetics (PKs) and pharmacodynamics of RO4929097in combination with temsirolimus. Methods Escalating doses of RO4929097 and temsirolimus were administered at three dose levels. Patients received once daily oral RO4929097 on a 3 days on/4 days off schedule every week, and weekly intravenous temsirolimus. Blood samples were collected for PK analysis. Archival tissue specimens were collected for Notch pathway biomarker analysis and genotyping of frequent oncogenic mutations. Results Seventeen patients with refractory advanced solid tumors were enrolled in three dose levels (DLs): DL1 (RO4929097 10 mg; Temsirolimus 25 mg), DL2 (RO4929097 20 mg; Temsirolimus 25 mg), and DL3 (RO4929097 20 mg; Temsirolimus 37.5 mg). The most common toxicities related to the study drug combination included: fatigue (82 %; grade 3 6 %), mucositis, (71 %; grade 3 6 %), neutropenia (59 %; grade 3 12 %), anemia (59 %; grade 3 0 %), and hypertriglyceridemia (59 %; grade 3 0 %). Two dose-limiting toxicities, grade 3 rash and grade 3 mucositis, were observed in the same patient in the first dose level prompting dose expansion. Eleven patients (73 %) had stable disease as their best response. Co-administration of RO4929097 was associated with increased clearance and reduced exposure to temsirolimus, suggestive of drug-drug interaction via CYP3A4 induction. No correlation between the expression of Notch pathway biomarkers or genotype and time to progression was noted. Conclusions RO4929097 can be safely combined with temsirolimus in patients with advanced solid tumors. The RP2D was established at 20 mg of RO4929097 combined with 37.5 mg of temsirolimus. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10637-013-0001-5) contains supplementary material, which is available to authorized users.